Critical, Reflective, Creative Thinking and Their Reflections on Academic Achievement - Akpur, Ugur (ELSEVIER SCI LTD, 2020)
The present study was conducted with the aim of examining the structural relationship pattern among critical thinking, reflective thinking and creative thinking and their predictive power on academic achievement. To this end, a total of 227 students, 127 (56 %) male and 100 (44%) female, attending a state university preparatory classes in Istanbul, Turkey, formed the study group. The Critical Thinking Scale, The Reflective Thinking Scale and The Marmara Creative Thinking Dispositions Scale were administered to the study group as data collection tools. To measure the academic achievement, the participants' overall average of grades, set by the institution, during the fall term of 2019-2020 academic year was taken as a basis. The collected data were analysed by applying SEM through AMOS 16 software program. The findings from the data revealed that critical thinking, reflective thinking and creative thinking correlated with each other in a positive and significant way and these variables all predicted academic achievement positively and significantly.
Keywords: Critical Thinking; Reflective Thinking; Creative Thinking; Academic Achievement; Foreign Language Learning; SKILLS; Education & Educational Research